GENOTYPES AND SERUM LEVELS OF APOLIPOPROTEIN E AND PARAOXONASE 1 IN CALCIFIC AORTIC VALVE STENOSIS - E. V. Shcheglova; A. I. Laipanova; M. K. Baikulova; Z. K. Chotchaeva; S. Sh. Rogova; V. N. Kolesnikov; O. I. Boeva (Российский кардиологический журнал, 2017)
Aim. Apolipoprotein E (apoE) and paraoxonase 1 (PON1) participate in regulation of blood lipoprotein levels, as well as in their hydrolysis and oxidation. We assumed that individual alleles of the apoE and PON1 genes, along with the changes in concentrations of these substances, contribute to the development of calcific aortic valve stenosis (CAVS).Material and methods. The study group included 108 patients with CAVS and 46 patients without any signs of the aortic valve lesions were determined. The serum apoE and PON1 levels were measured by ELISA, the Leu28Pro mutation in the apoE (rs429358) gene and the Gln192Arg mutation in the PON1 (rs662) gene were detected using PCR SNP-EXPRESS electrophoresis detection scheme.Results. Increased serum levels of apoE (0,05 vs 0,03 µg/l, p<0,001) and PON1 (4,8 vs 3,4 µg/ml, p<0,05) were detected in CAVS patients. The frequencies of allelic polymorphisms of the apoE and PON1 genes were similar in the two groups. 28Pro allele of the apoE gene was associated with increased level of low density lipoproteins in CAVS (3,9±1,05 vs 3,13±1,08 mmol/l, p<0,02) and total cholesterol in the controls (6,2; 6,5 vs 5,11±0,89 mmol/l, p<0,05). The PON1 genotype had no effect on lipid metabolism in CAVS patients. Controls with 192Gln allele demonstrated decreased blood levels of apoE (0,02 vs 0,05 µg/l, р<0,01) and increased PON1 serum concentration (4,1 vs 3,3 µg/ml, р<0,01).Conclusions. CAVS patients have increased serum levels of apoE and PON1; the apoE level is an independent predictor of aortic calcification. Polymorphic markers Gln192Arg of the PON1 gene and Leu28Pro of the apoE gene are not associated with CAVS.